2004
DOI: 10.1523/jneurosci.0086-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Glucocorticoids Are Essential for Maintaining Prefrontal Cortical Cognitive Function

Abstract: Glucocorticoid hormones are important in the maintenance of many brain functions. Although their receptors are distributed abundantly throughout the brain, including the prefrontal cortex (PFC), it is not clear how glucocorticoid functions, particularly with regard to cognitive processing in the PFC. There is evidence of PFC cognitive deficits such as working memory impairment in several stressrelated neuropsychiatric disorders, including depression, schizophrenia, and Parkinson's disease. Disruption of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(104 citation statements)
references
References 53 publications
(77 reference statements)
2
95
1
6
Order By: Relevance
“…Although the extent to which these hormonal changes are responsible for the structural and functional changes we observed in our obese rats remains unknown, some evidence suggests a causal link. For example, reduced glucocorticoid levels have been associated with diminished dendritic spine density in the PFC (38) and impaired performance on PFC-dependent cognitive tasks (39). The relative protection of the hippocampus during early stage obesity may be due to the temporary ability of elevated circulating leptin levels to compensate for reduced glucocorticoid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although the extent to which these hormonal changes are responsible for the structural and functional changes we observed in our obese rats remains unknown, some evidence suggests a causal link. For example, reduced glucocorticoid levels have been associated with diminished dendritic spine density in the PFC (38) and impaired performance on PFC-dependent cognitive tasks (39). The relative protection of the hippocampus during early stage obesity may be due to the temporary ability of elevated circulating leptin levels to compensate for reduced glucocorticoid levels.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the rhythm of CORT not only increases spines but also supports the survival of newly formed spines. Other studies showed that the spatial memory (which is hippocampal dependent) and working memory (which is prefrontal cortex dependent) were impaired by ADX (Conrad et al 1997, Mizoguchi et al 2004. Furthermore, ADX rats show depression-like behavior in the rotarod test (Mizoguchi et al 2008).…”
Section: Concentration-dependent Functions Of Non-stress Level Of Cormentioning
confidence: 96%
“…These differences seem not to depend on the intensity of the stress protocol since similar results were also obtained using handling, a milder stress challenge (Segovia et al 2008a,b). Since different studies have shown that corticosterone can modulate dopamine levels in the PFC (Imperato et al 1989;Mizoguchi et al 2004;Ago et al 2009), it is possible that the reduced increases of dopamine are secondary to the lower increases of corticosterone observed in the PFC of the EC rats. This would be in agreement with the reduction of stress-evoked dopamine release after blockade of GRs locally within PFC (Butts et al 2011).…”
Section: Acute Stress Dopamine and Acetylcholine In The Pfcmentioning
confidence: 99%